Decision Support System for Determining the Best Nurse at RSUD Porsea Using the Simple Additive Weighting Method - Situmorang, Rafael (Marcha Institute, 2024)
A decision support system is a combination of individual intelligence sources with component capabilities to improve decision quality. Decision support system is also a computer-based information system for decision-making management that handles semi-structured problems. The purpose of this study was to create an application for nurse employees at RSUD Porsea. Based on the results of the research that has been discussed, the Decision Support System for Determining the Best Nurse at RSUD Porsea using the Simple Additive Wieghting (SAW) method with the benefit of being able to make it easier to process nurse data and make it easier to determine the best nurse for a nurse promotion at RSUD Porsea.